An effective branch-and-bound algorithm for the maximum s-bundle problem - Zhou, Yi; Lin, Weibo; Hao, Jin-Kao; Xiao, Mingyu; Jin, Yan (European journal of operational research, 2022)
•We exploit the properties of the maximum s-bundle problem.•A branch-and-bound algorithm is proposed for the maximum s-bundle problem.•We study novel multi-branching techniques.•Numerical results show the benefit of the new algorithm compared to existing ones. An s-bundle (where s is a positive integer) is a connected graph, the vertex connectivity of which is at least n−s, where n is the number of vertices in the graph. As a relaxation of the classical clique model, the s-bundle is relevant for representing cohesive groups with an emphasis on the connectivity of members; thus, it is of great practical importance. In this work, we investigate the fundamental problem of finding the maximum s-bundle from a given graph and present an effective branch-and-bound algorithm for solving this NP-hard problem. The proposed algorithm is distinguished owing to its new multi-branching rules, graph coloring-based bounding technique, and reduction rules using structural information. The experiments indicate that the algorithm outperforms the best-known approaches on a wide range of well-known benchmark graphs for different s values. In particular, compared with the popular Russian Doll Search algorithm, the proposed algorithm almost doubles the success rate of solving large social networks in an hour when s=5.